BLUE GIANTS IN CASSIOPEA AND PERSEUS - GONZALEZ, G; GONZALEZ, G (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1954)
A list is given of 76 stars classified on objetive prism plates as belonging to the natural group OB. The stars included in the present list were found on plates taken with the 26-30 inch Tonantzintla Schmidt Camera and a 4-degree objetive prism.
BOL OBS TONAN TACUB
Keywords: BLUE GIANTS, CASSIOPEA, PERSEUS; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS